Prevalence of Dementia and Its Associated Factors in Cotonou Teaching Hospital, Benin - GNONLONFOUN, DIEU-DONNÉ; ADJIEN, KODJO CONSTANT; Ossou-Nguiet, Paul Macaire; Diallo, Lansana Laho; Houannou, Octave; ACAKPO, Jocelyn; Goudjinou, Gérald; Houinato, Dismand; AVODE, DOSSOU GILBERT (My University, 2014)
Introduction: Dementia constitutes a public health hazard in developing countries. There is little data in the sub-Saharan region of African especially in Benin. Objective: Determining dementia hospitalization prevalence and identifying its associated factors in CNHU-HKM, Cotonou. Method: It was a cross-sectional, prospective, descriptive and analytical research conducted from October 2012 to July 2013 in the neurology department; it involved 251 patients aged 50 and above. Dementia screening was conducted using a modified and adapted Mini Mental Scale Examination (MMSE). Dementia clinical and etiological diagnoses were respectively conducted based on DMS-IV and HACHINSKI criteria. Results: Patients were averagely aged 60.9 ± 8.1. Sex ratio (Male/Female) was 1.07. Dementia prevalence was 8.8%. This rate increased proportionally with age, from 5.3% with patients aged below 60 to 12.7% with patients aged above 60. Degenerative dementia was the most predominant type (50%). Following multi-varied analysis, smoking (RC = 6.05 [IC 95% = 1.26 - 29.38] p = 0.0001) and stroke past records (RC = 6.05 [IC 95% = 1.26 - 29.38] p = 0.001) revealed to be the factors associated with dementia. Conclusion: This research showed that dementia affects a significant part of the aging population in CNHU-HKM. It is imperative to combat its associated factors so as to defuse its prevalence.
Keywords: Prevalence; Dementia; Associated Factors; Cotonou